Efficient Synthesis of Aza-Phenanthroindolizidine and Aza-Phenanthroquinolizidine and Anticancer Activities - Wang, Kailiang; Wang, Wenlong; Wang, Qingmin; Huang, Runqiu (Letters in Organic Chemistry, 2008)
Aza-modifications of phenanthroindolizidine and phenanthroquinolizidine alkaloids were firstly designed to produce two aza-analogues, 13a-azatylophorine and 14a-aza-7-methoxylcryptopleurine starting from hydrazine monohydrate with high overall yields, respectively. The synthesis highlighted that some kinds of reactions were ameliorated in methodology. The newly synthesized target molecules including their salt derivatives were evaluated for anticancer activities against the BEL-7402 human liver cancer cell line and MOLT-4 human leukemia cell line. They exhibit anticancer activities.
Keywords: alkaloid